The CATCH checklist to investigate adult‐onset hypogonadism. (10th June 2018) - Defeudis, G.; Mazzilli, R.; Gianfrilli, D.; Lenzi, A.; Isidori, A. M.
Summary: Adult‐onset hypogonadism is a syndrome often underdiagnosed, undertreated, or incompletely explored. There are various reasons for this: firstly, undefined age range of men in whom testosterone levels should be investigated and then no definitive serum cutoff point for the diagnosis of hypogonadism; and finally, variable and non‐specific signs and symptoms; men and physicians do not pay adequate attention to sexual health. All these factors make the diagnostic criteria for hypogonadism controversial. The evaluation of the clinical features and causes of this syndrome, its link with age, the role of testosterone and other hormone levels, and the presence of any comorbidities are all useful factors in the investigation of this population. The purpose of this manuscript, after an accurate analysis of current literature, is to facilitate the diagnosis of hypogonadism in men through the use of the CATCH acronym and a checklist to offer a practical diagnostic tool for daily clinical practice. A narrative review of the relevant literature regarding the diagnosis of late‐onset hypogonadism or adult‐onset hypogonadism was performed. PubMed database was used to retrieve articles published on this topic. A useful new acronym CATCH (Clinical features [symptoms] and Causes, Age, Testosterone level, Comorbidities, and Hormones) and a practical checklist to facilitate the evaluation of hypogonadism in aging men were used. The evaluation of the clinical features and causes of hypogonadism, the link with age, the role of Testosterone and other hormones, and the evaluation of comorbidities are important in investigating adult‐onset hypogonadism. The CATCH checklist could be helpful for clinicians for an early diagnosis of both hypogonadism and associated comorbidities. We suggest the use of this acronym to advocate the investigation of declining testosterone in aging men.